Dampak dari Sikap Overprotective Orang Tua terhadap Anak Usia Dini - Khaira Shafia (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2024)
An overly protective parenting approach towards early childhood can hinder the child’s holistic development. This study shows that an overprotective attitude can hinder the growth of children’s independence, decision-making ability and social skills. In addition, children who are overprotected tend to have low self-confidence, have difficulty managing emotions, and lack a sense of responsibility. Lack of opportunities to learn from mistakes and limited social interaction further exacerbate this condition. On the other hand, a supportive parenting style, with parents as facilitators, allows children to develop their potential optimally and become independent individuals who are able to adapt to the social environment.